2011
DOI: 10.1136/ard.2011.152223
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab plus methotrexate is superior to methotrexate alone in the treatment of psoriatic arthritis in methotrexate-naive patients: the RESPOND study

Abstract: ObjectiveTo compare the efficacy and safety of treatment with infliximab plus methotrexate with methotrexate alone in methotrexate-naive patients with active psoriatic arthritis (PsA).MethodsIn this open-label study, patients 18 years and older with active PsA who were naive to methotrexate and not receiving disease-modifying therapy (N=115) were randomly assigned (1:1) to receive either infliximab (5 mg/kg) at weeks 0, 2, 6 and 14 plus methotrexate (15 mg/week); or methotrexate (15 mg/week) alone. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
104
1
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(126 citation statements)
references
References 22 publications
6
104
1
10
Order By: Relevance
“…And, as with depression, the administration of proinflammatory cytokines [e.g., interleukin (IL)-6] is associated with the perception of fatigue [49]. Further, treatment with cytokine antagonists is associated with a decrease in fatigue-administration of exogenous IL-1ra (anakinra) decreases fatigue in patients with Sjögren's syndrome [50], and the tumor necrosis factor (TNF)-α receptor antagonist infliximab and the IL-6 receptor antagonist toclizumab reduce fatigue in patients with cancer and autoimmune diseases [51][52][53][54][55].…”
Section: The Contribution Of Inflammation To Depression and Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…And, as with depression, the administration of proinflammatory cytokines [e.g., interleukin (IL)-6] is associated with the perception of fatigue [49]. Further, treatment with cytokine antagonists is associated with a decrease in fatigue-administration of exogenous IL-1ra (anakinra) decreases fatigue in patients with Sjögren's syndrome [50], and the tumor necrosis factor (TNF)-α receptor antagonist infliximab and the IL-6 receptor antagonist toclizumab reduce fatigue in patients with cancer and autoimmune diseases [51][52][53][54][55].…”
Section: The Contribution Of Inflammation To Depression and Fatiguementioning
confidence: 99%
“…Treatment with exogenous IL-1ra (anakinra), for instance, decreases fatigue in patients with Sjögren's syndrome [50]. Similarly, the TNF-α receptor antagonist infliximab and the IL-6 receptor antagonist tocilizumab reduce fatigue in patients with cancer [51] and a variety of autoimmune diseases [52][53][54][55]. Fatigue is a particularly prevalent problem for patients with multiple sclerosis (MS) [117].…”
Section: Therapeutic Approaches To the Treatment Of Fatigue: A Focus mentioning
confidence: 99%
“…In particular, studies analyzing the efficacy of oral DMARDs have shown no improvement over placebo in the case of methotrexate [26,27] and small effect sizes for sulfasalazine [28]. One phase IIb study did reveal efficacy for leflunomide for the joints only, but a phase III study was never performed [29].…”
Section: Challenges In the Treatment Of Psoriatic Arthritismentioning
confidence: 99%
“…The treatment of PsA with a combination of 2 conventional disease‐modifying antirheumatic drugs (DMARDs) 20, 21 or a DMARD plus a TNF inhibitor has been reported 10, 11, 15, 22. However, clinical trials simultaneously inhibiting 2 cytokines, TNF and IL‐17A, with biologics have not been reported in patients with PsA.…”
mentioning
confidence: 99%